Selection of the Most Appropriate Renewable Energy Alternatives by Using a Novel Interval-Valued Neutrosophic ELECTRE I Method - Karasan, Ali; Kahraman, Cengiz (VILNIUS UNIV PRESS, 2020)
Today energy demand in the world cannot be met based on the growing population of the countries. Exhaustible resources are not enough to supply this energy requirement. Furthermore, the pollution created by these sources is one of the most important issues for all living things. In this context, clean and sustainable energy alternatives need to be considered. In this study, a novel interval-valued neutrosophic (IVN) ELECTRE I method is conducted to select renewable energy alternative for a municipality. A new division operation and deneutrosophication method for interval-valued neutrosophic sets is proposed. A sensitivity analysis is also implemented to check the validity of the proposed method. The obtained results and the sensitivity analysis demonstrate that the given decision in the application is robust. The results of the proposed method determine that the wind power plant is the best alternative and our proposed method's decisions are consistent and reliable through the results of comparative and sensitivity analyses.
Keywords: interval-valued neutrosophic sets; ELECTRE I; multi-criteria decision making; renewable energy; MULTICRITERIA DECISION-MAKING; TOPSIS METHOD; OUTRANKING APPROACH; 2 DECADES; INFORMATION; MANAGEMENT; CONSENSUS; LOCATION; RANKING; NUMBERS; Computer Science; Mathematics